Factors contributing to the poor acceptance of non-Muslims towards Takaful Malaysia products: a study on promotional strategy / Erlia Nasir - Nasir, Erlia (Faculty of Business and Management, 2006)
Syarikat Takaful Malaysia Berhad was incorporated on the 29th November 1984 with an authorized capital of RM500 million and a paid up of RM 10million. It commended operation on the 22nd of July, 1985 prior to its official launching on the 2nd August 1985 by then Prime Minister of Malaysia, Tun Dr. Mahathir Mohamed. This research tries to evaluate the acceptance of Takaful Malaysia insurance among non-Muslim customers. This research will focus on the effectiveness of current promotion tools and strategies for Family Takaful products done by Takaful Malaysia.